The impact of early and late childcare experience on cognitive functions - A.Z. Békefi; J. Kárpáti; J. Futó (European Psychiatry, 2022)
Introduction Previous studies have found long lasting cognitive delays among children with early childcare experience, especially institutionalised experience. However, little is known about institutions’ effect in late childhood.